Magnetic relaxation in a Co(ii) chain complex: synthesis, structure, and DFT computational coupling constant. Issue 6 (20th January 2021) - Wu, Wen-Hao; Wang, Ya-Qun; Mi, Hong-Li; Xue, Qing-Xuan; Shao, Feng; Shen, Fei; Yang, Feng-Lei
Abstract : We report a homospin non-solvated Co II chain compound constructed by two similar tridentate ligands and chloride ions, which displays slow magnetic relaxation below 5 K. Abstract : A novel high-spin Co(ii ) complex, named [Co II 2 (μ-L1 )(μ-L2 )(μ-Cl)Cl] n (1 ), was achieved through the reaction of Co(ii ) salts with two kinds of pyrazolate ligands (HL1 = 2-(5-methyl-1 H -pyrazol-3-yl) pyridine; HL2 = 2-(5-methyl-4 H -1, 2, 4-triazol-3-yl)phenol) using a solvothermal method. Structurally, two types of Co(ii ) ions, octahedral and tetrahedral, bridged by three types of linkers (μ-Cl, μ-(N–N), μ-O), extend into 1D chains. Additionally, the interchain connections are weak, facilitating the occurrence of single-chain magnetic behavior. Magnetically, considerable frequency dependence of slow magnetic relaxation is observed below 5 K and the compound behaves like a single-chain magnet. Both the simulation of the coupling constant from the χ M T vs. T curve and DFT computations reveal that the μ-O linker in the Co2 O2 system transmits ferromagnetic coupling.